Social and economic outcomes from VET in schools for people with disabilities: Initial findings from an Australian national longitudinal study - Cocks, Errol; Thoresen, Stian (AVETRA Association, 2013)
Low workforce participation contributes to social and economic exclusion of people with disabilities. The lack of vocational opportunities and pathways in the transition from school can trap people with disabilities into non-vocational alternatives to employment with poor employment prospects. [Vocational education and training] VET and VET in schools (VETiS) are strong vocational pathways with good employment outcomes, particularly VET or VETiS which includes some form of work-based training such as apprenticeships and traineeships. This paper presents initial findings from a three-year national longitudinal study into social and economic outcomes for apprenticeship and traineeship graduates with disabilities funded by [National Centre for Vocational Education Research] NCVER. The paper will account for social and economic outcomes reported among the subset of research participants who undertook their training as part of VETiS (n=56). Initial findings suggest strong social and economic graduate outcomes. Australian policy encourages people with disabilities actively to participate in the workforce to the full extent of their abilities although available supports to initiate and sustain a vocational pathway such as VETiS can be improved. Increasing the evidence base of graduate outcomes can also encourage more people with disabilities to embark on a vocational pathway in the transition from school.